Impact of Blended Learning on Students' Creative Thinking Skills in Wave and Optics Course - Nisrina, Nina; Verawati, Ni Nyoman Sri Putu (Lensa: Jurnal Kependidikan Fisika, 2024)
Creative thinking skills are essential competencies that students must develop, particularly in physics education, which involves problem-solving and the application of complex concepts. One effective method for enhancing these skills is blended learning, which combines both face-to-face and online learning. This study aims to examine the impact of blended learning on the creative thinking skills of students in the Basic Physics course, specifically in the topics of Waves and Optics. The research used a quasi-experimental design with a pre-test and post-test approach, involving 20 first-semester students selected through purposive sampling. Data analysis was conducted using the N-gain formula by Hake to measure improvements in students' creative thinking skills, which included indicators of fluency, flexibility, originality, elaboration, and sensitivity to problems. The results showed a significant improvement in students' creative thinking skills, with an average pre-test score of 44.65 and a post-test score of 84.25, yielding an N-gain of 70.56%, which falls into the high category. Based on these findings, it can be concluded that blended learning is effective in enhancing students' creative thinking skills, particularly in the context of basic physics education. The implementation of blended learning positively contributes to the development of students' creativity through a combination of face-to-face and online learning.